Cdc45/Mcm2-7/GINS complex down-regulation mediates S phase arrest in okadaic acid-induced cell damage. (15th September 2018) - Feng, Mei; Zhou, Mi; Fu, Ling-ling; Cai, Jiang-jia; Ji, Lin-dan; Zhao, Jin-shun; Xu, Jin
Abstract: Okadaic acid (OA) is one of the most common and widespread marine toxins and causes acute gastrointestinal symptoms known as diarrheic shellfish poisoning (DSP) in humans. Although OA is not classified as a typical neurotoxin, an increasing number of studies have reported its neurotoxic effects. However, most of the available studies have focused on OA-induced inhibition of serine/threonine protein phosphatases, while the molecular mechanism of OA-induced neurotoxicity remains largely unclear. To better understand the potentially toxicological profile of OA, cell cycle arrest, DNA damage and alterations in gene expression in the human neuroblastoma cell line SHSY5Y upon OA exposure were determined using flow cytometry, comet assay, and transcriptome microarray. The results showed that OA could induce cell cycle arrest at S phase and might be involved in significant DNA strand breaks. Gene expression profiling indicated that the differentially expressed genes after OA exposure were significantly enriched in the "DNA replication" and "cell cycle" pathways. Real-time PCR result had further validated that down-regulation of the Cdc45/Mcm2-7/GINS complex might be the major factor regulating those alterations. These findings provide new insight into the molecular mechanisms of OA-induced neurotoxicity, and the current data may also provide a basis for future studies. Highlights: Toxicogenomic approach as a tool to investigate the neurotoxicity of OA. Gene expression profiling reveals that "DNA replication" and "cell cycle" as the major causes due to OA exposure. OA induces cell cycle arrest at S phase. OA induces S phase arrest and DNA damage probably due to down-regulation of the Cdc45-MCM-GINS complex.